Panton-Valentine leucocidin gene in methicillin resistant Staphylococcus aureus isolated from tertiary care hospital in Nepal - Gopiram Syangtan; Laxmi K Khanal; Shrijana Bista; Arun B Chand; Bijaya L Maharajhan; Prabin Dawadi; Reshma Tuladhar; Shiba K Rai; Dev R Joshi (Journal of Infection in Developing Countries)
Introduction: Methicillin-resistant Staphylococcus aureus (MRSA) expresses the Panton-Valentine leukocidin (PVL) virulence gene, which is associated with community and hospital-acquired severe MRSA infections. The objective of this study was to determine the prevalence and antibiotic susceptibility profile with a focus on the presence of the PVL gene among MRSA isolates in healthcare settings.